Un nouvel élan interaméricain en faveur de la justiciabilité des droits sociaux?: Retour, un an après, sur l’arrêt de la Cour Interaméricaine des Droits de l’Homme Muelle Flores c. Pérou du 6 mars 2019 - Gonzalez-Palacios, Carlos (2020)
Although the Pact of San José does not recognize the direct justiciability of social rights, the proliferation of cases relating to retirement pensions had the effect of questioning the Inter-American Court, first of all about its powers in matters of social security and, secondly, on the definition of the content of article 26 of the Pact of San José. In the case of Muelle Flores v. Peru, the judge rules for the first time on the right to retirement as an integral part of economic, social and cultural rights, which is part of a case law favorable to the justiciability of social rights.